Regulation of Public Finances in Slovenia in Light of Financial Constitutionality - Bohinc, Rado (Regulation of Public Finances in Light of Financial Constitutionality: Analysis on Certain Central and Eastern European Countries, 2022)
The purpose and the objectives of this chapter is to present briefly some of the legal theory of finance, followed by information on recent developments and current challenges in financial law and to present relevant financial institutions in the Republic of Slovenia (RS). This chapter is comprised of four subchapters. The first subchapter deals with the legal theory of finance, presenting theoretical views on public finance and financial law, about legal nature of the public budget, further on the legal theory of finance and on theoretical views related to constitutional provisions and the performance of the economy. The second subchapter deals with the public finances developments and trends in Slovenia, followed by brief description of fiscal system in Slovenia and some facts on management of public property. The third subchapter presents financial institutions in Slovenia. Ministry of finance, constitutional (Court of Audit and the Central Bank) and other financial institutions are briefly presented as follows: the Financial Administration, Agency for public oversight of auditing, Securities market agency, Ljubljana stock exchange, Slovenian sovereign holding and public institutions and public funds in general. The fourth subchapter presents current and planned regulatory challenges; it presents resilience and recovery measures, current measures to mitigate the effects of the COVID-19 epidemic and information on some of the planned future legislative initiatives.KEYWORDS: The legal theory of finance, public finance, financial law, public budget, management of public property. financial institutions in Slovenia, Court of audit, Central bank, Financial administration, Agency for public oversight of auditing, Securities market agency, Ljubljana stock exchange, Slovenian sovereign holding, public institutions, public funds in general, resilience and recovery measures.